The relationship between personal resources and job crafting on work engagement among Gen Y employees in SME bank, Kuala Lumpur / Nur Suhaila Amiruddin, Nazirah Anuar and Nursyazwani Ahmad Zubir - Amiruddin, Nur Suhaila; Anuar, Nazirah; Ahmad Zubir, Nursyazwani (2019)
Work engagement is defined as harnessing of organization members’ selves to their work roles and in engagement, people employ and express themselves physically, cognitively, and emotionally during role performance. The aims of this study are to determine the relationship between personal resources and work engagement, and the relationship between job crafting and work engagement. There are many factors that lead to work engagement such as social support, job autonomy, flexible work arrangement, job demands, occupational trust, unpleasant work circumstances and emotional exhaustion. Instead of all those factors, it is interested to look at the factors of job crafting and psychological capital. The study also analysed the current trend of SME Bank, Kuala Lumpur through identified it strengths, weaknesses, opportunities and threats which will be later developed into strategies and recommendations. In this study, quantitative method has been adopted and 300 set of questionnaires have been distributed to Gen Y employees in SME Bank, Kuala Lumpur. In findings, there are positive significant relationship between personal resources (self-efficacy) and work engagement, personal resources (optimism) and work engagement, job crafting (social job resources) and work engagement. While, personal resources (organizational based self-esteem) have no significant relationship with work engagement. Other than that, job crafting (structural job resources, hindering job demands and challenging job demands) also have no significant relationship with work engagement. By conducting this study, it can give clear overview to the researcher on how work engagement emerges and the influences factors of work engagement. Besides, it will fill the gap of the body of knowledge and also add to existing literature on personal resources, job crafting, and work engagement.